Development and Characterization of Ramipril Loaded Solid self Nanoemulsifying Drug Delivery System SNEDDS for Improved Oral Delivery of Lipophilic Drugs - Kasturi, Madhavi (International Journal of Pharmaceutical & Biological Archive, 2016)
Development and Characterization of Ramipril Loaded Solid self Nanoemulsifying Drug Delivery System SNEDDS for Improved Oral Delivery of Lipophilic Drugs